SPACE CATEGORY IN THE LINGUISTIC LANDSCAPE OF LATGALE REGION - Pošeiko, Solvita (Via Latgalica, 2012)
The space is a significant parameter of world’s existence, and a component making human’s experience and the view of the world; any culture’s understanding of the underlying principles of world’s formation, human’s place and purpose within it is associated with it. Language signs of the linguistic landscape are one of the external factors promoting and influencing formation of the world and its feeling, as well as territorial identity, overcoming or narrowing geographical and psychological borders.The object of the research – a category of the space in the linguistic landscape of four administrative- territorial units – Daugavpils, Rēzekne, Līvani cities and Vārkava district, the object – language signs with a word or word compound explicitly expressing space.The aim of the research – to find out how and with which language means language signs with additional space indications make concepts on space and feeling of identity to a certain area in Latgale regional linguistic landscape.A method of the linguistic landscape was used to collect data, a content analysis was important for data selection; post-structural and descriptive methods were applied to develop the research.Basic categories of the space within the context of the linguistic landscape are as follows: language space, information space, geographical space and public space, as the existence of the language signs are not possible outside them. The selected language signs confirm that words and word compounds representing real and mythical space are additionally given in the linguistic landscape of Latgale region.The most significant conclusions:1. The most often used words expressing space in the linguistic landscape of the research areal are: nomenclature words – a centre, a shop, a bank, a salon, a pharmacy, a school – and place-name Latgale (all of them are mentioned more than 20 times). The most involved words in making word compounds – a centre, and a salon (e. g., Centre of Friends; Fortunetelling Salon, Salon of Alcoholic Drinks).2. The language signs expressing actual space are predominant – house-names (e. g., a shop, a bank, a pharmacy, a bar, etc.) related to the public and material area, and place-names (Latgale, Rēzekne, Vārkava, Daugavpils, Līvani). A choice of house-names suggests that human needs, desires and opportunities to meet them are set as a primary issue; money circulation is the main criterion for movement through the space. Usage of place-names, in its turn, proves that the larger is the territorial unit, the more seldom it is additionally emphasized in the language signs.3. Features characterizing mythical space – polycentrism – creation of several centres and a sign even in the level of one street (e. g., there are pharmacies of 2 different companies the „Pharmacy Centre of Līvāni” in Rīga Street in Līvāni); worlds or lands of self-made goods or services (e. g., Photo World, Health Island, Alkoland, etc.); usage of words related to the celestial area – „above” (e. g., Moon Pharmacy, Sun Store, Cloud, Star Bookstore, etc.). Focusing on oneself, and things that are familiar, close and secure.